Investigating the Organizational Citizenship Behavior and Identifying its Relationship with the Components of Work Ethics in Staff Staff in Tehran University of Medical Sciences and Health Services - Zohreh Barkand; Mina Jamshidi; Hossein Dargahi; Saeed Sayad Shirkesh (Tehran University of Medical Sciences, 2019)
Background and Aim: In todaychr('39')s challenging world, the ethical issues of work as a requirement in organizations have always been discussed and its relevance to organizational citizenship behavior as a kind of antitrust behavior has always been raised. The aim of this study was to determine the relationship between organizational citizenship behavior and work ethic among the staffs of the faculties of Tehran university of medical sciences in 2016-2017. Materials and Methods: The present research was descriptive-analytic and the statistical population of the study was 426 employees of colleges. They were selected according to the Cochran formula as proportional sample and selected by random sampling. Organizational citizenship behavior inventory (1988) and Grigory, et al, Patty (1990) questionnaire, whose validity was assessed by the experts. The cronbachchr('39')s alpha coefficient, organizational citizenship behavior inventory (0.793), and job ethics (0.764), represent the internal consistency of the questionnaire. For analysis of variables, descriptive statistics and spearman correlation test were used and kolmogorov-smirnov test was used to normalize the data. Results: Most male respondents, aged between 20-30 years; in terms of graduate degrees, were in a professional contract with a record of 5-10 years. Results showed that there was a positive and significant relationship between organizational citizenship behavior and work ethics (p=0.783). Conclusions: Higher organizational citizenship behavior leads to higher levels of work ethics. Therefore, by training and strengthening organizational citizenship behavior, the level of work ethics among employees can be improved.